Inhomogeneous Helmholtz equations in wave guides – existence and uniqueness results with energy methods - SCHWEIZER, BEN (European journal of applied mathematics, 2023)
The Helmholtz equation $-\nabla· (a\nabla u) - ω^2 u = f$ is considered in an unbounded wave guide $Ω := \mathbb{R} × S \subset \mathbb{R}^d$ , $S\subset \mathbb{R}^{d-1}$ a bounded domain. The coefficient a is strictly elliptic and either periodic in the unbounded direction $x_1 \in \mathbb{R}$ or periodic outside a compact subset; in the latter case, two different periodic media can be used in the two unbounded directions. For non-singular frequencies $ω$ , we show the existence of a solution u . While previous proofs of such results were based on analyticity arguments within operator theory, here, only energy methods are used.